Analisis Pengaruh Penerapan Etika Bisnis Terhadap Kepuasan Konsumen Toko Della Muda di Desa Madiredo - Afi Faida Maulidia; Noor Shodiq Askandar; Abdul Wahid Mahsuni (Universitas Islam Malang, 2023)
The purpose of this study was to find out and analyze the application of fairness, honesty and trust to customer satisfaction at Toko Della Muda in Madiredo Village. The type of data used in this study is the primary data type. The subjects of this research are consumers of Della Muda stores. Sampling in this study used a probabilistic random sampling method by distributing questionnaires. Through paper distributed to consumers at the Della Muda Store in Madiredo. From the calculations, a sample of 96 respondents was obtained. The results of this study are to find out whether fairness, honesty and trust affect consumer satisfaction. It is concluded that simultaneous testing can be seen that fairness, honesty and trust simultaneously affect consumer satisfaction. Partial testing can be seen that fairness, honesty and trust simultaneously have a significant positive effect on customer satisfactionKeywords: Fairness, honesty, trust and customer satisfaction